2020
DOI: 10.1007/s00425-020-03426-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CsERF2 in leaf variegation of Cymbidium sinense ‘Dharma’

Abstract: Main conclusion CsERF2, an ethylene response factor, plays a role in leaf variegation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Previously, we observed that the chloroplast ultrastructure of leaf‐colour mutants of C . sinense showed abnormal starch granule enlargement (Gao et al ., 2020 ), which indicated that sugar metabolism was abnormal in the chloroplast. Sugars are the primary end product of CO 2 assimilation and act as a retrograde signal to modulate expression of nuclear‐encoded PS genes (Rolland et al ., 2006 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we observed that the chloroplast ultrastructure of leaf‐colour mutants of C . sinense showed abnormal starch granule enlargement (Gao et al ., 2020 ), which indicated that sugar metabolism was abnormal in the chloroplast. Sugars are the primary end product of CO 2 assimilation and act as a retrograde signal to modulate expression of nuclear‐encoded PS genes (Rolland et al ., 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…sinense have focused on traditional biology such as embryology, physiology, genetic diversity and population structure (Huang et al ., 1998 ; Li and Zhang, 2016 ; Lu et al ., 2011 ). Recent research involves micropropagation (Gao et al ., 2014 ), chemical variation in essential oils (Li et al ., 2017 ) and the unigenes associated with flower development (Su et al ., 2018a , 2018b , 2018a , 2018b ; Zhang et al ., 2013 ), leaf colour variation (Gao et al ., 2020 ; Zhu et al ., 2015 ) and the origin of pelorism (Su et al ., 2018b ). However, for specific traits that model plants lack, such as unique perianth development, purple‐black flower colour and fragrance (Hsu et al ., 2015a ; Kim et al ., 2016 ; Pan et al ., 2014 ), research methods for isolation of homologous genes by a reverse genetic strategy are severely restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Such kinds of mutants in which variegated leaves can be stably inherited and preserved make it possible for artificial selection and the development of new ornamental cultivars. Accordingly, the coloration mechanisms of variegated leaves mutants aroused more interests and have been studied at multiple levels in multiple species [ 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In plant species other than Arabidopsis , it was found that mutation in chlorophyll a apoprotein A1 gene could lead to variegation in Helianthus annuus L. [ 12 ]. In Cymbidium sinense , the ethylene response factors (ERFs) gene CsERF2 played crucial roles in leaf variegation [ 13 ]. Moreover, data showed that disruption of carotene biosynthesis in Brassica napus also led to abnormal plastids and variegated leaves [ 14 ].…”
Section: Introductionmentioning
confidence: 99%